Strategies for Promoting & Integrating Renewable Energy Resources in UAE - Al-Amir, Jawaher Hassan (2011)
Power is a critical infrastructure input and the lifeblood of the development and growth of the economy of any country. Renewable Energy (RE) supplies are of increasing environmental and economic importance in all countries. Moreover, RE forms an important component in future energy supplies for the electricity supply industry. This research looks into moving energy policy in the UAE in the direction of sustainability to turn the UAE into a leading country in a new environmental field. The research covers UAE current energy policy especially relevant to RE as well as the current situation and future targets. Furthermore, the research looks into different countries and different case studies that have used RE. Moreover, best practices and applicable strategies to the UAE will be highlighted. A plan for the same was proposed and feedback from concerned authorities and stakeholders in the UAE were be considered to come up with a revised plan that can promote RE in the country. The findings showed that implementation of RE technologies are possible and can be applied in the UAE through different stages gradually. A draft policy was prepared and was revised based on stakeholder feedback. Moreover, the plan proposed was designed to be implemented in three stages (short, medium and long term). Some of the main components include a deregulation move in the emirate, country and gulf levels through different stages. Other components of the policy include access to the grid which is improved at each stage, as well as financial incentives and implementation of a Feed-In Tariff. Stakeholder Feedback from the Federal Ministry and Dubai Electricity and Water Authority was used to refine the policy.